Papel do protomero A da toxina pertussis na inibição in vivo da migração de neutrófilos e respostas inflamatórias leucócito-dependentes - Brito, Gerly Anne de Castro (1995)
Pertussis toxin (PT), produced by Bordetella pertussis, is composed of two subunits, namely A protomer and B oligomer. The A protomer (SI subunit) has ADP-ribosyltransferase activity that catalyzes the transfer of ADP-ribose from NAD to a regulatory GTP-binding protein (G protein) in eukaryotic cells. The B oligomer (S2:S3:2S4:S5) contributes to the adhesion of B. pertussis to the target cells. The aim of these experiments was to investigate the effect of PT on polymorphonuclear leukocytes (PMNs) migration and on cell-dependent inflammatory responses in vivo. A PT analog (PT 165-9K/129G) with two amino acid substitutions in SI subunit and with no ADP-ribosyltransferase activity was used to determine which part of PT molecule was accountable for its actions. The results of this work showed that, different from PT 165-9K/129G (PTm), intravenous injection of PT significantly inhibits neutrophil migration induced by LPS and fMLP in a dose dependent fashion. Moreover, PT was also able to significantly (p < 0.05) block mononuclear phagocytes migration to peritoneal cavities induced by thioglycolate in a dose dependent fashion, while PTm was not able to produce this action. Unlike PTm, PT significantly (p < 0.05) inhibited cell-dependent inflammatory responses such as edema induced by carrageenin and the increase in vascular permeability induced by LTB4. Neither PT nor PTm was capable of inhibiting the edema induced by dextran and the vascular permeability induced by histamine or bradykinin. It could be also observed that PT and PTm, when injected into peritoneal cavities, were able to induce neutrophil migration in a dose dependent fashion. These data suggest clearly that PT exerts an antiinflammatory effect, which seems to be mainly due to the ADP-ribosiltransferase activity of the A protomer in a G protein, resulting in its inactivation. Furthermore, they suggest that the PT selectin-like portion (B oligomer) does not contribute substantially to inhibit the leukocyte migration. However, neutrophil migration induced by PTm seems to occur independently of SI catalytic activity. Thus, the B oligomer seems to be responsible for this activity.